2005
DOI: 10.1007/s00264-005-0679-x
|View full text |Cite
|
Sign up to set email alerts
|

Floating knee injuries: long-term results of four treatment methods

Abstract: One hundred twenty-four consecutive patients with true floating knee injury presented between 1987 and 2001. They were treated with non-operative, operative (external fixation and intramedullary nailing) and combined modalities. Sixty patients were followed up, at an average of 7.2 years, for age, gender, type of trauma and fracture; time to fracture union and time to mobilisation. Complications that were encountered and return to normal activities were recorded. Better and comparable union rates of fractures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 18 publications
2
41
0
4
Order By: Relevance
“…Earlier return to activities and higher excellent and good long-term functional results were observed among patients who underwent intramedullary nailing. External fixation of the fractured femur resulted in decreased range of movement at the knee due to quadriceps muscle fixation [20]. We found, like the majority of authors, that the use of intramedullary nailing in this kind of trauma leads to a low incidence of non-union, infectious complications, and malunion.…”
Section: Discussionmentioning
confidence: 57%
“…Earlier return to activities and higher excellent and good long-term functional results were observed among patients who underwent intramedullary nailing. External fixation of the fractured femur resulted in decreased range of movement at the knee due to quadriceps muscle fixation [20]. We found, like the majority of authors, that the use of intramedullary nailing in this kind of trauma leads to a low incidence of non-union, infectious complications, and malunion.…”
Section: Discussionmentioning
confidence: 57%
“…Dwyer et al15) used the combined modalities of treatment with one fracture managed conservatively and the other surgically. They concluded that the treatment method for the tibia did not interfere with joint mobilization 15).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the treatment method for the tibia did not interfere with joint mobilization 15). Lundy and Johnson1) recommended surgical stabilization of the fractures for early mobilization, which produced the best results.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The predictive factors for poor outcome are Fraser type II fractures, the presence of considerable bone comminution and/or skin opening, as well as the initial presence of an arterial lesion. 5,8 There have been few articles on floating knee in the literature, with less than thirty series published, often collecting few cases and with varied treatment strategies. 2,4,8,13 The largest series published is that of the traumatology study group (GETRAUM), reported by Pietu involved 172 cases occurring in patients over 15 years of age.…”
Section: Case Reportmentioning
confidence: 98%